2020
DOI: 10.1039/d0ob00690d
|View full text |Cite
|
Sign up to set email alerts
|

Radiopharmacological evaluation of a caspase-3 responsive probe with optimized pharmacokinetics for PET imaging of tumor apoptosis

Abstract: A PET imaging probe with optimized pharmacokinetics was designed for real-time monitoring of the activity of caspase-3 in tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…273,274 Alternatively, the N-terminal Cys can react with 2-cyano-6-aminobenzothiazoles (CBTs), as demonstrated in the synthesis of imaging agents for positron emission tomography (PET). 269,275 For formation of disulfide bonds using an orthogonal protecting group strategy, StBu must be removed before other protecting groups to avoid cleaving or scrambling existing disulfides (as would occur upon treatment with a reducing agent). This is typically done on-resin prior to TFA acidolysis, which can result in side products and low yields.…”
Section: Benzyloxymethyl (Bom)mentioning
confidence: 99%
“…273,274 Alternatively, the N-terminal Cys can react with 2-cyano-6-aminobenzothiazoles (CBTs), as demonstrated in the synthesis of imaging agents for positron emission tomography (PET). 269,275 For formation of disulfide bonds using an orthogonal protecting group strategy, StBu must be removed before other protecting groups to avoid cleaving or scrambling existing disulfides (as would occur upon treatment with a reducing agent). This is typically done on-resin prior to TFA acidolysis, which can result in side products and low yields.…”
Section: Benzyloxymethyl (Bom)mentioning
confidence: 99%
“…This may lead to a low baseline uptake of radioactivity. Nowadays, a number of 18 F-ICMT-11 analogs, including FITI, have been synthesized and investigated preclinically in order to obtain probes with much more favorable biodistribution properties [30,31]. Furthermore, the development of radiolabeled caspase substrates was also expected to solve the problem of binding site saturation.…”
Section: Apoptosis Imaging In Healthy Volunteers: Targeting Caspasementioning
confidence: 99%
“…More recently, Lin and coworkers have reported a similar peptide probe for PET imaging of tumor apoptosis (Figure 2C). [ 67 ] The probe was activated by caspase‐3 to undergo intermolecular cyclization and the subsequent formation of nanosized (≈138 nm) particles. The authors demonstrated increased tumor accumulation of the labeled peptide in mice treated with doxorubicin (a chemotherapeutic agent known to increase expression levels of active caspase‐3) when compared with untreated animals, confirming that the activation of the probe and formation of nanoparticles are essential to improve concentration of radioactivity in the target tissue.…”
Section: Size or Shape Reconfiguration Upon Endogenous Stimulusmentioning
confidence: 99%
“…Adapted with permission. [ 67 ] Copyright 2020, Royal Society of Chemistry. D) Myeloperoxidase‐induced activation of a PET probe was demonstrated in mouse models of myocardial infarction.…”
Section: Size or Shape Reconfiguration Upon Endogenous Stimulusmentioning
confidence: 99%